The Influence of Job Placement and Competence on Employee Work Motivation - Nugraha, Andi (Greenation International Journal of Economics and Accounting, 2024)
The purpose of this research is to determine and analyze: 1)Placement 2)Competence; 3)Employee Work Motivation; and 4)The Influence of Placement and Competence on Employee Work Motivation at UPTD Road and Bridge Management Service Area II of the West Java Province Public Works and Spatial Planning Office, both simultaneously and partially. The research method used in this study is descriptive survey and explanatory survey, with the unit of analysis being the employees of UPTD Pengelolaan Jalan dan Jembatan Wilayah Pelayanan II Dinas Bina Marga dan Penataan Ruang Provinsi Jawa Barat Azzakiyyah Bandung, with a sample size of 31 people. The type of investigation is causal, and the time horizon in this study is cross-sectional. Based on the research results, it was found that the placement of Madrasah Ibtidaiyah employees is still not appropriate, the competencies of UPTD Pengelolaan Jalan dan Jembatan Wilayah Pelayanan II Dinas Bina Marga dan Penataan Ruang Provinsi Jawa Barat employees can generally be said to still be inadequate, and the work motivation of UPTD Pengelolaan Jalan dan Jembatan Wilayah Pelayanan II Dinas Bina Marga dan Penataan Ruang Provinsi Jawa Barat employees is currently rated as good. Employee placement and competencies simultaneously and partially affect the work motivation of UPTD Pengelolaan Jalan dan Jembatan Wilayah Pelayanan II Dinas Bina Marga dan Penataan Ruang Provinsi Jawa Barat employees. However, partially, Placement predominantly affects the work motivation of employees more than competence. Since placement more dominantly influences the work motivation of employees, it becomes the first priority in improving their work motivation. Therefore, the PTD Pengelolaan Jalan dan Jembatan Wilayah Pelayanan II Dinas Bina Marga dan Penataan Ruang Provinsi Jawa Barat is advised to consistently manage employee placements according to their abilities, so that they can work more professionally.